Effect of Paving Runway and Atmospheric Conditions on Airplane Takeoff Distance and Time - A.R Yass, Muhammad. (Anbar Journal of Engineering Sciences, 2019)
This paper study the effect of paving runway and atmospheric conditions on airplane takeoffdistance and time with roll stage and air stage. Two airplane types DC-9 and Boeing 747-400were considered for different atmospheric condition with different weight by using time stepintegration technique and Krenkel and Salzman assumed that the variation of thrust andvelocity create the balance of forces equations on the aircraft during its takeoff run. The airtemperature and airplane weight and runway paving are the most effected parameters ontakeoff time and distance. The runway paving consideration are very important for airportdesign and runway construction to minimums fuel consumption during takeoff